Developing Insurance Markets : Motivations and Initiatives to Grow the Institutional Investment Role of Emerging Market Insurers - Thorburn, Craig (World Bank, Washington, DC, 2021)
This paper develops a theme identified in recent insurance sector development work: that more developed insurance markets are desirable as insurers play a more effective institutional investment role, whether this objective seeks deeper and more liquid bond or capital markets, or to see more investment in long term assets such as infrastructure or in support of climate finance. It explores the perspective of domestic insurers, summarizing positions regarding asset selection and key drivers of current and desired asset structures. The paper draws on interviews in several deep-dive countries supplemented by additional engagement for a more representative global reach. It then discusses a range of solutions that may be considered by policymakers categorized under efforts to: grow the sector so it can play a more substantive role; improve how assets are packaged and made available to insurance companies so they are more investable; review risk-based capital rules to ensure that they encourage and reward the right behavior; and check other regulations do not present unintended barriers. The paper concludes that, although domestic insurers are interested in making investments that meet these goals, they are constrained by barriers that are almost entirely external to their own operations and outside their control. With some adjustment to supply and regulatory settings, insurers should translate their interest into action, increasing their role and improving the contribution to this desirable development outcome. The paper is intended to be particularly relevant for policymakers and practitioners with less experience within insurance company operations who are looking to better understand and respond to insurance decision making.